Association between adult height, myocardial infarction, heart failure, stroke and death: a Korean nationwide population-based study. (5th September 2017) - Park, Chan Soon; Choi, Eue-Keun; Han, Kyung-Do; Lee, Hyun Jung; Rhee, Tae-Min; Lee, So-Ryoung; Cha, Myung-Jin; Lim, Woo-Hyun; Kang, Si-Hyuck; Oh, Seil
Abstract: Background: The association between adult height and cardiovascular (CV) events and mortality has been suggested, albeit inconsistently. We sought to discover the comprehensive relationship between height, CV-related morbidity and all-cause death according to age. Methods: We investigated the association between adult height and myocardial infarction (MI), heart failure (HF), stroke incidence and mortality in 16 528 128 Korean patients who underwent regular health check-ups (2005–08). Height was stratified by decile according to age (20–39 years, 40–59 years and ≥60 years) and gender. Results: During a 9-year follow-up period, 590 346 participants died and 232 093 were admitted to hospital for MI, 201 411 for HF and 267 566 for stroke. An inverse relationship between height and MI, HF, stroke and all-cause death was observed in the overall cohort analysis. The association was unchanged after adjusting for CV risk and behavioural and adulthood socioeconomic factors. Both male and female sex showed an inverse relationship with height in adulthood, CV events and mortality. Adult height showed an inverse association in all CV events and mortality, especially in the older groups (≥40 years). In a subgroup analysis of body mass index, there was an inverse relationship between height, CV events and mortality in each group. Conclusions: Shorter height in adulthood was strongly related to an increased risk of MI, HF, stroke and all-cause death. A suitable environment and appropriate nutrition early in life could influence adult height and eventually reduce the risk of CV events and mortality.